Дочки-матери на выживание: [роман] / Юлия Лавряшина - Лавряшина Юлия Александровна (Э, 2017)
Экземпляры: Селтинская районная библиотека (аб) (20180620) / Инвентарный номер: 205316 / Цена: / Авт.знак: Л13 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6